The Authenticity Scale: Validation in Russian Culture - Nartova-Bochaver, Sofya; Reznichenko, Sofia; Maltby, John (Frontiers in Psychology, 2021)
The correlational study is aimed at validating the Authenticity Scale in Russian culture. Authenticity is considered a trait responsible for a person’s ability to be oneself. It helps people resist environment pressure and prevent self-alienation, which contributes to maintaining psychological wellbeing. The original Authenticity Scale includes three subscales: Authentic Living, Accepting External Influence and Self-Alienation. In total, 2,188 respondents (Mage = 26.30, SDage = 13.81; 78.1% female) participated in the survey. The dimensionality of the Authenticity Scale and its measurement invariance across sex, age, and depression rate subgroups was examined with exploratory and confirmatory factor analyses; the original tripartite structure was kept. Convergent validity was tested through correlation analyses with the Warwick-Edinburgh Mental Well-being Scale, the International Positive and Negative Affect Schedule Short-Form, the Centre of Epidemiological Studies-Depression Scale, the Rosenberg Self-Esteem Scale, and the Satisfaction with Life Scale. According to the CFA results, the structure of the Russian version differs from the original one slightly (item 1 was moved from the subscale Authentic Living to the subscale Accepting External Influence and item 4 was excluded); however, the modified factor model showed the best absolute and comparative fit statistics (CFI = 0.961, TLI = 0.949, RMSEA = 0.050 (90% CI, 0.40; 0.60) and SRMR = 0.037). The reliability (McDonald's Omega) of the Authenticity Scale subscales was satisfactory and ranged from 0.78 to 0.84. It was revealed that youth are more likely to have high scores on Accepting External Influence and Self-Alienation than adults. Men and women did not significantly differ on the sub-scores of Authenticity Scale. Multigroup CFA also showed that Authenticity Scale scores may be biased in people with high levels of clinical depression, in terms of the item intercepts. Authentic Living is positively connected with mental wellbeing, self-esteem, positive affect, satisfaction with life, and negatively with depressive symptoms and negative affect; reverse trends were found for Accepting External Influence and Self-Alienation subscales. The Russian version of Authenticity scale is a valid, reliable tool that may be recommended for use in various areas of non-clinical practice.